Made In U.K. Assembly Line 'Pans' For Trinidad - Unknown (Trinidad Guardian)
Steelband Promotions of Croydon, England is planning to export to Trinidad, steelband instruments which have been already running off the assembly line. The system of producing the musical instruments have eliminated the use of oil drums and substitutes a purpose-made instrument that only needs to be tuned. The new method is more productive and advance than the traditional ones used ever since the steelband originated in Trinidad and Tobago.
Keywords: Steel drum (Musical instrument) -- Manufacturing processes -- England -- London; Steel drum (Musical instrument) -- Trinidad and Tobago; Steel band music -- England -- London; Steel drum (Musical instrument) -- Construction -- England -- London